Interface passivation of liquid‐phase crystallized silicon on glass studied with high‐frequency capacitance–voltage measurements. Issue 7 (25th February 2016) - Preissler, Natalie; Töfflinger, Jan Amaru; Shutsko, Ivan; Gabriel, Onno; Calnan, Sonya; Stannowski, Bernd; Rech, Bernd; Schlatmann, Rutger
Abstract : The passivation quality at the interface between dielectric interlayer (IL) stacks and liquid‐phase crystallized silicon (LPC‐Si) was investigated by means of high‐frequency capacitance–voltage ( C – V ) measurements. The developed device structure was based on a molybdenum layer sandwiched between the glass substrate and the IL/LPC‐Si stack. C – V curves were discussed in terms of hysteresis formation and capacitance relaxation. We varied the nitrogen and hydrogen content in the a‐SiO x N y :H layer adjacent to the LPC‐Si and studied the effects on the defect state density at the IL/LPC‐Si interface ( D it ) as well as on the effective charge density in the IL ( Q IL, eff ). Both parameters are crucial for the analysis of chemical and field‐effect passivation. Furthermore, the effect of an additional hydrogen plasma treatment (HPT) on D it and Q IL, eff was investigated. A Gaussian‐like defect distribution at around 0.1 eV above the mid gap energy is significantly reduced by the additional HPT. With additional HPT, the lowest D it and highest Q IL, eff at mid gap, i.e., D it  = (3.5 ± 0.7) × 10 11  eV −1  cm −2 and Q IL, eff  = (1.6 ± 0.3) × 10 12  cm −2, correspond to the passivation by an a‐SiO x N y :H layer with a low nitrogen and high hydrogen content.